Role of skeletal muscle on impaired insulin sensitivity in rats fed a sucrose-rich diet: Effect of moderate levels of dietary fish oil - D'alessandro, Maria Eugenia Guadalupe (2000)
In the present study we investigated: (1) the contribution of the skeletal muscle to the mechanisms underlying the impaired glucose homeostasis and insulin sensitivity present in dyslipemic rats fed a sucrose-rich diet (SRD) over a long period of time and (2) the effect of fish oil on these parameters when there was a stable hypertriglyceridemia before the source of fat (corn oil) in the diet was replaced by isocaloric amounts of cod liver oil. Our results show an increased triglyceride content in the gastrocnemius muscle with an impaired capacity for glucose oxidation in the basal state and during euglycemic clamp. This was mainly due to a decrease of the active form of pyruvate dehydrogenase complex (PDHa) and an increase of PDH kinase activities. Hyperglycemia, normoinsulinemia, and diminished peripheral insulin sensitivity also were found. Even though there were no changes in the insulin levels, the former metabolic abnormalities were completely reversed when the source of fat was changed from corn oil to cod liver oil. The data also suggest that in the gastrocnemius muscle of rats fed a SRD over an extended period, an increased availability and oxidation of the lipid fuel, which in turn impairs the glucose oxidation, contributes to the abnormal glucose homeostasis and to the peripheral insulin insensitivity. Moreover, the parallel effect on insulin sensitivity, glucose, and lipid homeostasis attained through the manipulation of dietary fat (n-3) in the SRD suggests a role of n-3 fatty acid in the management of dyslipidemia and insulin resistance. Copyright (C) 2000 Elsevier Science Inc.